2012
DOI: 10.1111/j.1365-2516.2012.02770.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment trends for haemophilia A and haemophilia B in the United States: results from the 2010 practice patterns survey

Abstract: Frequent evaluation of haemophilia treatment is necessary to improve patient care. The 2010 Practice Patterns Survey (PPS) investigated current trends in haemophilia treatment in the United States, as reported by nurses. The aim was to document practice patterns for haemophilia A and haemophilia B Survey questionnaires were sent to nurses at haemophilia treatment centres (HTCs) across the United States. Seventy-one of 126 HTCs (56%) responded to the survey. Factor dosage across treatment modalities ranged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 30 publications
1
70
1
Order By: Relevance
“…Consequently, inadequate degrees of adherence and concordance can result in higher bleeding rates [54,55]. Adolescents have 20-30% lower compliance than infants (aged <2 years) and adults (aged >25 years), and 2.5 times higher rates of bleeding events [56][57][58]. Therefore, an innovative approach to care aimed at improving compliance can have important effects on treatment outcomes [29] and represents a considerable achievement for all hemophilia stakeholders.…”
Section: Innovative Clinical Modelmentioning
confidence: 99%
“…Consequently, inadequate degrees of adherence and concordance can result in higher bleeding rates [54,55]. Adolescents have 20-30% lower compliance than infants (aged <2 years) and adults (aged >25 years), and 2.5 times higher rates of bleeding events [56][57][58]. Therefore, an innovative approach to care aimed at improving compliance can have important effects on treatment outcomes [29] and represents a considerable achievement for all hemophilia stakeholders.…”
Section: Innovative Clinical Modelmentioning
confidence: 99%
“…Recent surveys from Europe, reporting 6/14 countries had more than 50% of adults on prophylaxis [27], from Canada, where 43% of patients aged 31-70 years were on prophylaxis [28], and the USA where 33% of adults over 25 years were on continuous prophylaxis [29].…”
Section: Prophylaxis In Adultsmentioning
confidence: 99%
“…In general, it is more logical and cost-effective to "preserve" joints through prophylactic replacement therapy during childhood, than to start this treatment in adults with target joints per week or every other day [29,45]. For hemophilia, B this is twice a week 30-40 IU/kg.…”
Section: Prophylaxis In Adultsmentioning
confidence: 99%
“…So, effective pain management is extremely important for improvement quality of life among patients with haemophilia. However,current numbers of healthcare providers are not sufficient to provide access to the increasing demand for primary care and many primary care practices have no one available to provide the timeconsuming counseling and teaching of management skills to relief the clinical signs [22,23].Therefore several models are developed to promote pain self-management for haemophilics in chronic pain may be especially needed.While some observational studies show a lack of readiness to change and a typically low adherence to recommended treatments in patients with chronic pain [24][25][26]. Researchers believe that beliefs, attitudes, subjective norms, self-efficacy, and intentions in the manage-…”
Section: Management Of Pain In Haemophilia Patientsmentioning
confidence: 99%
“…The study found that a positive attitude and adherence can be enhanced if people have the opportunity to interact with peers who model and reinforce adherent behaviors [17][18][19][20][21][22][23][24][25][26][27][28][29]. Dictionary defines peer as one that is of equal standing with another: one belonging to the same societal group especially based on age, grade, or status.…”
Section: A Model For Pain Managemen:peer Educationmentioning
confidence: 99%